Kinematic Changes during Prolonged Fast-Walking in Old and Young Adults - Oliveira, Camila Fonseca; Vieira, Edgar Ramos; Machado Sousa, Filipa Manuel; Vilas-Boas, João Paulo (Frontiers in Medicine, 2017)
Walking biomechanics is known to be influenced by speed. However, most of the research examining the effects of walking speed and gait characteristics has been conducted after a fast-walking task, neglecting the changes that may occur during the task. The aim of the present study was to determine the impact of fast-walking over time on kinematics in young and old adults. Twenty-seven young adults (26.6 ± 6.0 years) and twenty-three old adults (71.0 ± 5.6 years) walked at 70% of their maximum heart rate for twenty minutes or until exhaustion, and the effects of fast-walking on spatial-temporal parameters and on angular kinematics were analysed during the activity. During the protocol, both age-groups increased step-width variability. Significant effects of time were found for the ankle and hip at toe off for the older group. For the younger group, only the ankle angle at heel strike changed over time. For both groups, fast-walking induced changes in the coordination among the lower-limb angles which were more prominent during the swing phase of the gait. In conclusion, lower-limb kinematics changes in young adults were compatible with early signs of fatigue. The increased step-width variability in old groups may indicate an augmented risk of falling. Changes in the walking kinematics of old adults suggest that the adjustments for weight acceptance and body propulsion were restricted to the hip and ankle joints. The kinematic changes among the lower-limb during the swing phase may compromise the quality of gait. These findings provide a foundation for future studies in the assessment of the risk of falls in older adults associated with walking at a faster pace.